Pengaruh Latihan Menggunakan Alat Bantu terhadap Keterampilan Chest Pass Pada Peserta Ekstrakurikuler Bolabasket di SMP Negeri 1 Kota Sukabumi - Maulana, Irvan; Maulana, Firman; Nurina, Titis (utile: Jurnal Kependidikan, 2019)
Basket ball is a sport group consisting of two teams, 5 people for each team. The puprose of the game is to get as many points as possible by entering the ball into the opponent's ring. This study has a purpose, namely to find out the effect of training to use tools on chest pass skills. And to find out using net tools, car tires and targets for chest pass skills at 1 Junior High School.This research used quasi-experimental design used "One Groups Pretest-Postest Design". The research design that has a pretest before being treat and posttest after being treated. Test results data analyzed through normality test, homogeneity test, and hypothesis test (t test) using Microsoft Excel 2010 application to find out the results of the study.Based on data analysis, this study shows that is a significant influence between training using tools, car tires and targets on basketball extracurricular applications at Sukabumi 1 Junior High School. This is evidenced by the fact that t count is 9.150> 1.71 (t-table) and the magnitude of significance value p 1441.0 <0.05. So Ho is rejected and Ha is accepted, so it can be concluded that there is a significant effect of training using a tool for chest pass. When viewed from the Mean number of 6.68, this shows that there is an effect of training using a tool for chest pass skills.